UNBIODEGREDABLE (INERT) COD IN LEACHATE - Akkaya, Ebru; Demir, Ahmet; Varank, Gamze (YILDIZ TECHNICAL UNIV, 2011)
Leachate consists of resistant organic matter to biological degradation, to decide the most appropriate treatment method, it is significant to evaluate the biodegradability of leachate and determine the percentage of resistant organic matter. It is concluded in literature that, in biological treatment systems, inert products form when substrat biologically degrade and also it is stated that biological degradation of organic matter in waste water occurs in different mechanism and speeds. Solid waste leachate is composed of easily degraded, high concentrated, organic matter, unbiodegradable organic matter and inorganic ions. The products degradation of microbial activity is dissolved microbial products and particular inert organic matter. Biological treatment systems are inadequate for raw leachate treatment, because of existing high amount of inert COD. Since the existence of inert matter in treated leachate impedes providing discharge standards, additional treatment methods must be applied. In this study, sources of inert components in leachate, the relationship of inert components with landfill age, groups of organic components according to their molecular weight are studied. The importance of these inert COD studies in raw and treated leachate important in choosing the most appropriate treatment method.
Keywords: Leachate; inert COD; molecular weight; LANDFILL LEACHATE; ORGANIC-MATTER; ANAEROBIC TREATMENT; NANOFILTRATION; FRACTIONATION; PURIFICATION; REMOVAL; CARBON; Engineering